Meningkatkan Keterampilan Kerjasama Siswa dalam Belajar Fiqh melalui Metode Make-a-Match - Nasution , Fauziyyah Nur Azmi; Amien, Saiful; Thoifah , I’anatut; Mohammad Shahidul Islam (TADRIS: Jurnal Pendidikan Islam, 2024)
The study aimed to describe the impact of Fiqh learning actions using the Make-a-Match method on the cooperative skills of eleventh-grade students at Madrasah Aliyah Muhammadiyah 1 Kota Malang. This research used a qualitative approach with class action research (CAR) designed with two cycles. The study subjects were students in the 11th grade of the Department of Social Sciences Education (IPS), which had 18 students. Researchers collected data through observations, interviews, and documentation during the class action process. They then analyzed it through the Miles, Huberman, and Saldana procedures. Research results showed that the Make-a-Match method improved students' collaborative skills. Each of the collaborative skills indicators showed an improvement from cycle I to cycle II. The match-seeking technique required in applying this learning method instructed students to actively follow learning, be responsible as group members, interact, and collaborate.